Method for leakage measurement in the recirculation path of a hermetic pump. Issue 1 (March 2020) - Chaburko, P; Kuznetsov, A
Abstract: The article is devoted to the measurement of leakage in the recirculation path of a hermetic pump. The field of application of hermetic pumps is described. The mathematical model used in computer simulation and the mesh conditions are given. The results of the numerical modeling and the theoretical calculation are presented. The graph of the dependence of the leakage in the recirculation path on the pump head is shown. The scalar scenes of velocities and pressures in the c path are given.